Everything you need to ace math in one big fat notebook : the complete middle school study guide - Peterson, Altair (Big fat notebook., 2016)
A workbook that examines mathematics on a middle school level. Organized by key concepts, the text includes mnemonic devices, definitions, timelines and doodles to help the subject stick in your brain, so you can ace your class.--